Characterization of mechanical properties of Ultem® 9085 using FDM - Zhang, Yongjie (2018)
It is well known that for additive manufactured parts, mechanical properties are strongly influenced by the printing process parameters. This paper investigates the effect of the coupon shape and geometry on the mechanical properties, in particular, tensile strength of parts manufactured using Ultem® 9085, printed using Stratasys Fortus 900MC. Three different types of coupon geometry, namely ASTM D638 Type I, Type II and ASTM D3039 are tested according to the respective standard requirements, and it was that found that there is significant variation in the tensile strength between the specimens. Subsequently, fracture surface of the 3 different specimens are then examined under the Scanning Electron Microscope (SEM) to provide potential explanations for the difference in mechanical strength.